“Teaching Them That Pain Exists”: Dilemmas Regarding Memory Transmission and Entrepreneurship in Adult Children of Former Political Prisoners 40 Years After the Coup D’Etat in Chile - Palma, Evelyn (Journal of interpersonal violence, 2021)
The present study sought to identify and understand the memory transmission and entrepreneurship processes conducted by children of victims of politically motivated imprisonment and torture during Chile’s civilian-military dictatorship. A qualitative methodology was adopted, with an exploratory and analytic-relational design being used. Twelve children of former political prisoners, seven men and five women, participated in the study. Focus groups were selected as a data production technique. A content analysis was conducted following Grounded Theory guidelines. Results suggest that the adult sons and daughters of survivors have taken up memory transmission and entrepreneurship based on their parents’ memories of political imprisonment and torture. They engage in memory transmission and entrepreneurship by constructing exemplary memories about their parents’ experiences. They transmit these memories to peers and to their own children once they reach adulthood, given the increased openness of Chilean society regarding these discussions.